Credit Loan Selection During the Pandemic Recommendation MCDM-Promethee Method: - - Akmaludin, Akmaludin; Sihombing, Erene Gernaria; Dewi, Linda Sari; Rinawati, Rinawati; Arisawati, Ester (Sinkron : jurnal dan penelitian teknik informatika, 2020)
In the current state of COVID-19, many middle and lower-income businesses such as Micro, Small and Medium Enterprises (UMKM) have experienced a decrease in their income turnover, so that they require additional capital costs to carry on their business life. To provide additional capital loans, there are several requirements that must be met by every UMKM. Like an independent business that is carried out, whether it is permanent or only limited to domicile, then how long have they started the business they have built up to now, do they have collateral as loan guarantee, do they have a good level of business productivity during the running, seen from the report made, do you already have a lot of customers from the business you run. This is a benchmark for providing loans to UMKM. The method that can be recommended is Promethee, which is part of the Multi-Criteria Decision Making (MCDM) concept as a rating method in determining loan issues recommended by the Promethee method. The results obtained from the ranking with the Promethee method, namely that of the six selected and evaluated UMKM, the first rank was from the UMKM-3 with the highest weight value of 0.208, followed by UMKM-1 with a weight of 0.042 and followed by UMKM-5 which were still considered feasible even though they were not valuable. negative, while the other two UMKMs cannot be said to be eligible for a loan, namely UMKM-2 and UMKM-4 because they are negative.